Tridepsides as potential bioactives: a review on their chemistry and the global distribution of their lichenic and non-lichenic natural sources - Norouzi, Hooman; Sohrabi, Mohammad; Yousefi, Masoud; Boustie, Joel (Frontiers in Fungal Biology, 2023)
Tridepsides, as fully oxidized polyketides, have been known to exist in lichens for more than a century. Recent studies have showed that these possible defensive lichenochemicals possess various biological activities. Also, a candidate biosynthetic gene cluster was recently reported for gyrophoric acid (GA), an important tridepside. The present study focused on biosynthesis, natural sources, biological activities, and bioanalytical methods of tridepside molecules. Our survey shows that, so far, lichenic tridepsides have been reported from 37 families, 111 genera, and 526 species of lichen. Because many of their species contain tridepsides, the families Parmeliaceae, Lobariaceae, and Peltigeraceae can be considered critical lichenic sources of tridepsides. Furthermore, several species of Hypotrachyna in Parmeliaceae family showed lichenic tridepsides, suggesting that this genus is a viable source of tridepsides. This research also explored tridepsides from non-lichenic sources, such as non-lichenized fungi, lichenicolous fungi, endophytes, parasites, and liverworts, which offer substantial potential as biotechnological sources to produce tridepsides, which are produced in small amounts in lichen thalli. Two lichenic tridepsides have also been detected in non-lichenic sources: GA and tenuiorin (TE). Additionally, no significant correlation was found between tridepside biosynthesis and geographical distribution patterns for several potentially tridepside-producing lichens. We further showed that GA is the most studied tridepside with various reported biological activities, including anticancer, wound healing, photoprotection, anti-aging, antioxidant, cardiovascular effect, DNA interaction, anti-diabetes, anti-Alzheimer’s, anti-bacterial, and antifungal. Last but not least, this study provides an overview of some bioanalytical methods used to analyze tridepsides over the past few years.